POLICY MONETARY IN INDONESIA - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; Edi Riansyah; Hendri Sose Fauzi (RADJA PUBLIKA, 2026)
Monetary policy is one of the main macroeconomic policy instruments implemented by the central bank to maintain economic stability. In Indonesia, monetary policy is implemented by Bank Indonesia with the primary goal of achieving and maintaining the stability of the rupiah's value. This stability includes price stability, reflected in controlled inflation rates and the stability of the rupiah's exchange rate against foreign currencies. This article aims to analyze draft, objective, instrument, And challenge policymonetary in Indonesia. Method The method used in this study is a descriptive qualitative approach through a literature study sourced from books, laws and regulations, and official publications of Bank Indonesia. The results of the study indicate that Bank Indonesia implements monetary policy using several main instruments, including open market operations, policy interest rates, minimum reserve requirements, and discount facilities. These instruments are used in an integrated manner to control amount Moneycirculating, influence ethnic group flower market, as well as guard stability financial system. However, the implementation of monetary policy in Indonesia faces various challenges, such as global economic uncertainty, external inflationary pressures, the digitalization of the financial sector, and the need for coordination with fiscal policy. Therefore, an adaptive, credible, and data-driven monetary policy is crucial to supporting sustainable economic growth and national economic stability.